Vosaroxin in Combination With Cytarabine Provides a New Salvage Option for AML - Lederman, Lynne (MD Conference Express, 2014)
The addition of vosaroxin to cytarabine improves overall survival and complete remission rates in patients with relapsed, refractory acute myeloid leukemia. This combination is not associated with increased early mortality. Patients at least age 60 years seemed to benefit more than younger patients.